Patch reefs as sources of long and continuous skeletal records of horizontal reef expansion in Dongsha Atoll, South China Sea - Wei, Yi; Shen, Chuan-Chou; Soong, Keryea (Frontiers in Marine Science, 2022)
Atolls are annular midocean reefs with various topographical features. The reef rim of an atoll encloses a central lagoon and lagoonal patch reefs therein. Two hypotheses explaining the origins of patch reefs in atoll lagoons have been developed: the karst hypothesis and the growth hypothesis, which emphasize the role of uneven erosion and uneven timing of reef accretion (especially horizontal expansion), respectively, in the formation and growth of patch reefs. In this study, we investigated trends in the locations, depths, ages, sizes, and other features of flat-top and pinnacle-top reefs in the Dongsha Atoll in the South China Sea by analyzing bathymetric LiDAR images and performing U-Th dating on samples we collected from various reefs in the atoll. Three of our main findings were consistent with the growth hypothesis: (1) the differences in ages of the centers of different flat-top patch reefs reflected the different times at which each patch reef reached the surface and started to expand horizontally; (2) the top surfaces of individual flat-top patch reefs had old centers and young peripheries, reflecting horizontal growth; and (3) all the pinnacle-top reefs we examined had more live corals on their tips than on the surrounding bases. We observed no positive correlation between the ages of the centers and the diameters of flat-top patch reefs; that is, larger reefs did not necessarily have older centers, indicating that various complex factors affect the expansion and age patterns of patch reefs. Overall, the findings of this study provide support for the growth hypothesis and for the use of flat-top patch reefs as sources of easily accessible long-term coral skeletal records. They may therefore serve as a reference for future studies on asymmetric reef expansion and other relevant topics.